HSP90 and HSP70 Families in Lateolabrax maculatus: Genome-Wide Identification, Molecular Characterization, and Expression Profiles in Response to Various Environmental Stressors - Sun, Yalong; Wen, Haishen; Tian, Yuan; Mao, Xuebin; Li, Xiurong; Li, Junjie; Hu, Yanbo; Liu, Yang; Li, Jifang; Li, Yun (Frontiers in Physiology, 2021)
Heat shock proteins (HSPs) are a large class of highly conserved chaperons which play important roles in response to elevated temperature and other environmental stressors. In the present study, 5 HSP90 genes and 17 HSP70 genes were systematically characterized in spotted sea bass (Lateolabrax maculatus). The evolutionary footprint of HSP genes was revealed via the analysis of phylogeny, chromosome location and gene copy numbers. In addition, the gene structure features and the putative distribution of heat shock elements (HSEs) and hypoxia response elements (HREs) in the promoter regions were analyzed. The protein-protein interaction (PPI) networks analysis results indicated the potential transcriptional regulation between the HSF1 and HSPs and a wide range of interaction among HSPs. Furthermore, qPCR was performed to detect the expression profiles of HSP90 and HSP70 genes in gill, liver and muscle tissues after heat stress, meanwhile the expression patterns in gills under alkalinity and hypoxia stresses were determined by analyzing RNA-Seq datasets. Results showed that after heat stress, most of examined HSP genes were significantly up-regulated in a tissue-specific and time-dependent manner, and HSP90AA1.1, HSP90AA1.2, HSP70.1 and HSP70.2 were the most intense responsive genes in all three tissues. In response to alkalinity stress, 11 out of 13 significant regulated HSP genes exhibited suppressed expression patterns. Alternatively, among the 12 hypoxia-responsive expressed HSP genes, 7 genes showed induced expressions, while HSP90AA1.2, HSP70.1 and HSP70.2 had more significant up-regulated changes after hypoxic challenge. Our findings provide the essential basis for further functional studies of HSP genes in response to abiotic stresses in spotted sea bass.